Examining the Association Between Major Depressive Disorder and Coronary Heart Disease: A Structured Literature Review - McIntyre, Kevin; Schening, Hailey; Vaughan, Sarah (Université d'Ottawa | University of Ottawa, 2015)
Examining the Association Between Major Depressive Disorder and Coronary Heart Disease: A Structured Literature Review Kevin McIntyre, Hailey Schening, Sarah Vaughan Background: Cardiovascular Disease (CVD) is currently the number one cause of death globally and it is estimated that by the year 2020, depression will be the second leading cause of disability throughout the world. This literature review is focused specifically on coronary heart disease, a subset of cardiovascular disease, which involves the blood vessels supplying the heart muscle. Objective: The aim of this literature review is to assess the evidence regarding the presence of preexisting cases of Major Depressive Disorder (MDD) as an associated factor for developing Coronary Heart Disease (CHD) among the middle and older adult populations of the United States. Methods: Keywords: “Depression” OR “Major Depressive Disorder” AND “Coronary Heart Disease” OR “CHD” AND “Older Adults” OR “Middle Aged Adults” were entered into the PubMed, Web of Science, PsycINFO, and Google Scholar databases. The results were then reviewed after meeting the criteria of language (English), recency (published in the last fifteen years), location (conducted in the United States), and a sample population including middle aged and older adults (older adult defined as 60 years of age and older). Results: Of the articles found, ten met the inclusion criteria and were evaluated through this structured literature review. These studies determined that MDD does increase the risk of CHD among the middle aged and older population of the United States and may even increase the likelihood of CVD mortality. Conclusion: There is extensive evidence demonstrating the association between MDD and CHD. However, further research is required to determine the specific underlying mechanism(s).